Geographical Locations of Banks as an Influencer for Green Banking Adoption - Tara, Kanak; Singh, Saumya; Kumar, Ritesh; Sundararajan, Muniyan (Prabandhan: Indian Journal of Management, 2019)
The twenty first century began with strong initiatives towards environmental protection and sustainable development as advancements in operations such as transport, manufacturing and process, telecommunication, information technologies, and services etc. around the world became evident. The deteriorating environment at a rapid rate has raised an alarming demand for immediate steps towards protection of the environment and saving of the environment from further deterioration. Today, developmental activities look only at the economic benefits exploiting the limited natural resources in an unplanned and unchecked manner overlooking the needs of the future, and all industrial sectors in the world economy including the banking sector are facing huge challenges with environmental problems and their related impacts in day-to-day businesses. The banking sector and its role in sustainable development was studied through its new initiative to control environmental pollution in the very beginning level of seeking financial assistance for industrial activities and getting assurance from the proprietors, which is commonly recognized as green banking. In this paper, the effect of geographical locations of the respondents on green banking adoption was also studied through statistical analysis of the data collected using a specially designed questionnaire duly incorporating the factors of green banking. The study revealed that geographical locations of the banks played a significant role on the green banking adoption, but no impact was observed due to demographic parameters such as age, gender, experience, and position of the respondents.